Nanoparticles Targeted Drug Delivery System via Epidermal Growth Factor Receptor: a Review - Agus Rusdin; Nasrul Wathoni; Keiichi Motoyama; I Made Joni; Ronny Lesmana; Muchtaridi Muchtaridi (Indonesian Journal of Pharmaceutics, 2019)
Overexpressing of epidermal growth factor receptor (EGFR) in specific organ implicates tumour aggression and proliferation. Therefore, EGFR becomes a primary consideration for targeted cancer therapy. Nanoparticle drug delivery system is a promising multifunctional technique to provide the targeted drug delivery system. This review was aimed to discuss the nanoparticles formulation for targeted drug delivery system via EGFR. The data were collected from published journals recorded in the Scopus database. Various types of nanoparticles were widely studied to provide an EGFR-targeted drug delivery system. The formulations using specific targeting mediators were conjugated on several technologies such as polymeric nanoparticles, nanometals, and miscellaneous nanoparticles. Most of nanoparticles formulation become an excellent delivery carrier for drugs or gene to site-specific targeted by in vitro and in vivo evaluations. EGFR-targeted drug delivery system could be a promising technique to provide high effectiveness of drugs in EGFR-positive cells cancers with lower side effects to non-tumour cells.Keywords : Epidermal growth factor receptor, Cancer, Nanoparticle, targeted drug